1987
DOI: 10.1002/clc.4960101011
|View full text |Cite
|
Sign up to set email alerts
|

Early diastolic time intervals during hypertensive pregnancy

Abstract: Summary: Early diastolic time intervals have been assessed by means of the echopolycardiographic method in 17 pregnant women who developed hypertension during pregnancy (HP) and in 14 normal pregnant women (N). Systolic time intervals (STI), stroke volume (SV), ejection fraction (EF), and mean velocity of myocardial fiber shortening (VCF) were also evaluated. Recordings were performed in the left lateral decubitus (LLD) and then in the supine decubitus (SD). In LLD, isovolumic relaxation period (IRP) was prol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2011
2011
2011
2011

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 29 publications
0
1
0
Order By: Relevance
“…The hemodynamics of preeclampsia is a subject of controversies. Cross-sectional studies of women with preeclampsia have revealed diverse hemodynamic findings such as elevated cardiac output [2], high vascular resistance and reduced cardiac output [3] and reduced myocardial contractility [4]. The data on changes in left ventricular diastolic function is scarce.…”
Section: Introductionmentioning
confidence: 98%
“…The hemodynamics of preeclampsia is a subject of controversies. Cross-sectional studies of women with preeclampsia have revealed diverse hemodynamic findings such as elevated cardiac output [2], high vascular resistance and reduced cardiac output [3] and reduced myocardial contractility [4]. The data on changes in left ventricular diastolic function is scarce.…”
Section: Introductionmentioning
confidence: 98%